2014
DOI: 10.1186/s12879-014-0643-8
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus prevalence and type distribution among women attending routine gynecological examinations in Saudi Arabia

Abstract: BackgroundCervical cancer (CC) is caused by persistent infection with high-risk (HR) human papillomavirus (HPV) types. In Saudi Arabia which has a population of 6.5 million women over the age of 15 years, approximately 152 new cases of CC are diagnosed and 55 women die from the disease annually. Nevertheless current epidemiological data for HPV in this population are limited. This study evaluated the prevalence and type distribution of HPV and documented the awareness of HPV infection and health-related behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…Primary health care workers should play important roles as health educators and promoters. Therefore, it is essential that PHC physicians should have satisfactory knowledge and high compliance toward cancer cervix screening recommendations (Can et al, 2014). (31) Results of the present study showed that participants' knowledge grades regarding cervical cancer were quite suboptimal, where 42.3% were knowledgeable regarding cancer cervix, 16.1% were knowledgeable regarding screening guidelines, and 31.4% had overall knowledge.…”
Section: Discussion:-mentioning
confidence: 75%
See 1 more Smart Citation
“…Primary health care workers should play important roles as health educators and promoters. Therefore, it is essential that PHC physicians should have satisfactory knowledge and high compliance toward cancer cervix screening recommendations (Can et al, 2014). (31) Results of the present study showed that participants' knowledge grades regarding cervical cancer were quite suboptimal, where 42.3% were knowledgeable regarding cancer cervix, 16.1% were knowledgeable regarding screening guidelines, and 31.4% had overall knowledge.…”
Section: Discussion:-mentioning
confidence: 75%
“…The epidemiology of HPV infection among females in Saudi Arabia is not fully comprehended due to the lack of database and limited publications regarding prevalence and genotype. (4)(5)(6) Most of the HPV infections are transient and when it persists, the duration from initial infection to development of high-grade cervical neoplasia and invasive cancer take an average of 15 years. (7) Most of the risk factors for cervical cancer are associated with the increased risk of acquiring HPV infection.…”
mentioning
confidence: 99%
“…Their results showed that in a group of 417 women, HPV-DNA was detected in 9.8% women. The most prevalent HR-HPV types were HPV-68/73, HPV-18, and HPV-16, while the most common LR-HPV types were HPV-6, HPV-42, HPV-53, and HPV-54 [31].…”
Section: Hpv Prevalence In the General Population In Saudi Arabiamentioning
confidence: 99%
“…Another study that screened cervical cancer specimens in Saudi women reported that 89% of the specimens were HPV positive [37]. Eleven different HPV genotypes were detected, including the high-risk HPV- 16,18,31,39,45,51,59, and 73 and the low-risk HPV-6, 64, and 70. Consistent with previous studies, HPV-16 and HPV-18 were the most common genotypes.…”
Section: Hpv Prevalence Among Cervical Cancer Patients In Saudi Arabiamentioning
confidence: 99%
“…Recent studies using polymerase chain reaction (PCR) analysis conducted in Saudi Arabia, the largest in size and population of the GCC countries, show a relatively high prevalence of HPV infection [17][18][19]. One study investigated HPV 16/18 DNA prevalence among women attending a family medicine clinic for routine gynecological examinations in Riyadh, the capital of Saudi Arabia.…”
Section: Hpv and Cervical Cancer In Arabian Peninsula Countriesmentioning
confidence: 99%